Comparison of two methods for converting central venous values of acid-base status to arterial values in critically ill patients. (May 2021) - Shastri, Lisha; Boulain, Thierry; Rees, Stephen Edward; Thomsen, Lars Pilegaard
Highlights: Mathematical arterialization of venous blood in critically ill patients. Comparison of two methods – statistical and physiological based. Addition/removal of excess CO2 content beyond aerobic metabolism explains the discrepancies. Abstract: Background: Assessment of the critically ill patient requires arterial acid-base status. Venous blood could provide a surrogate, with methods transforming venous values to arterial, improving their utility. This manuscript compares two of these methods, a statistical and a physiological method. Where these methods are inadequate to describe critically ill patients, physiological mechanisms are explored to explain discrepancies. Methods: 1109 paired arterial and central-venous blood samples, from patients diagnosed with acute circulatory failure, were available for retrospective analysis. Of these, 386 samples were used previously to validate the statistical model. The statistical method of Boulain et al. 2016 and the physiological method of Rees et al. 2006 were applied to the 386 sample pairs, and compared using Bland-Altman analysis. A subset of the 1109 samples, where the physiological method could not accurately calculate arterial values, were analysed further to assess the necessary addition of CO2 or strong acid at the tissues to account for arterio-venous differences. Results: Bias (LoA) for comparison of calculated and measured arterial values ( n  = 386) were similar for the statistical method (pH: -0.003 (-0.051 to 0.045), PCO2 : -0.02 (-1.33 to 1.29 kPa)) and physiological method (pH: 0.009 (-0.033 to 0.052), PCO2 : -0.08 (-1.20 to 1.03 kPa)). In the 381 cases (of the 1109 sample pairs) defined as not accurately described, addition of a median CO2 concentration of 0.72 mmol/l in excess of aerobic metabolism, explained this for 333 cases, with the remainder requiring simultaneous strong acid transport. Conclusion: Both methods appear equal in their ability to transform central-venous values to arterial, albeit warranting caution when using either in a critically ill population. The physiological approach was able to describe arterio-venous differences not explained by aerobic metabolism alone.